2023
DOI: 10.1186/s12889-022-14969-x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of anti-SARS-CoV-2 antibodies and factors associated with infection among adolescent men who have sex with men and transgender women in Salvador, Brazil

Abstract: Background Brazil was strongly affected by the COVID-19 pandemic and the impact of the pandemic on sexual and gender minorities’ youth remains unknown. This study aimed to estimate the seroprevalence of SARS-CoV-2 antibodies and associated factors among adolescent men who have sex with men (AMSM) and transgender women (ATGW) participants of a human immunodeficiency virus (HIV) pre-exposure prophylaxis cohort study (PrEP1519). Methods This is a cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…There is a need to reach and inform a large number of adolescents from the key population about HIV prevention. Twenty percent of adolescent MSM and TGW reached out by the demand creation strategies of PrEP1519 did reach the PrEP clinics [45,52]. Online interventions can be more cost-effective and easily scaled up to increase service coverage.…”
Section: Plos Onementioning
confidence: 99%
“…There is a need to reach and inform a large number of adolescents from the key population about HIV prevention. Twenty percent of adolescent MSM and TGW reached out by the demand creation strategies of PrEP1519 did reach the PrEP clinics [45,52]. Online interventions can be more cost-effective and easily scaled up to increase service coverage.…”
Section: Plos Onementioning
confidence: 99%
“…2 , 3 Despite the high number of cases, Brazil has one of the lowest rates of diagnosis when compared to other countries. 4 …”
Section: Introductionmentioning
confidence: 99%
“…When compared to studies evaluating populations with other co-infections, similar values were observed in the literature when compared to our work. A Brazilian study 8 detected anti-SARS-CoV-2 in 20.4 % among people living with HIV with no information on the prevalence of hepatitis among these individuals. This high prevalence may reveal that this population is exposed to SARS-CoV-2 even during a period of social isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Low-income countries’ investments in public health are often insufficient in these settings,7 leading to increase in the number of under-reported cases 8 9. For example, the prevalence of anti-S IgG antibodies for SARS-CoV-2 in an extremely socioeconomic vulnerable population in Rio de Janeiro and Salvador before vaccine implementation was higher than previous estimates for these cities, indicating the significant burden of COVID-19 in these communities 10 11. The unavailability of diagnostic tools is aggravated by the arrival of new SARS-CoV-2 variants, also contributing to under-reporting of cases 8 9…”
Section: Introductionmentioning
confidence: 99%